Using Online Peer-Mentoring to Empower Young Adults with End-Stage Renal Disease: A Feasibility Study - Zheng, Kai (American Medical Informatics Association, 2010)
Patients with end-stage renal disease must receive a kidney transplant or live on dialysis. Either treatment option introduces radical changes to their lifestyles and may result in significant psychosocial disruptions. Among these patients, young adults (YAs)—between age 18 and 30—are confronted with unique challenges because their life course is yet to be defined and their adulthood identity has not fully emerged. Partnering with the National Kidney Foundation of Michigan, we experimented with a web-based “peer-mentoring” intervention to create a user-driven, self-sustained online community. The objective was to help YAs develop “new normal” lives, restore social identities, and regain confidence in school and work. To foster a comforting online atmosphere for this vulnerable population, it is critical to use tailored technology designs catering to their needs and concerns. In this paper, we describe a prototype that we developed—ktalk.org, and report our findings from pilot-testing it with 38 YAs.